Going solo the extraordinary rise and surprising appeal of living alone - Klinenberg, Eric 1970- (Penguin Books, 2013)
Renowned sociologist and author Eric Klinenberg explores the dramatic rise of solo living and examines the seismic impact it's having on our culture, business, and politics